Strategi Pengembangan Obyek Wisata Pusat Edukasi Gajag Sumatera (Elephas maximus spp. sumatranus) Aek Nauli Bagi Pengembangan Wilayah Kabupaten Simalungun - Darmasyah, Buana; Sihombing, Benteng; N. Sihaloho, Arvita (Median : Jurnal Ilmu Ilmu Eksakta, 2025)
Research entitled "Development Strategy of Sumatera Elephant Education Center (Elephas Maximus Sumatranus) Tourism Object Aek Nauli for the Development of Simalungun Regency" has been conducted with the aim of knowing the existing condition of the Sumatera elephant education center Aek Nauli tourism object and to analyze the existing condition and determine the development strategy of the Sumateran elephant education center tourism object related to the development of Simalungun Regency. The research method was carried out using the opinion method of 48 respondents of visitors and managers of the Sumatera elephant education center tourism object. The existing condition of the management of the Sumatera elephant education center tourist attraction has strong internal strengths in terms of strategic location, unique tourism, elephant health that is always prime and a very neat tourism experience, has low weak internal weaknesses especially in terms of the absence of a legal basis for the application of entrance fees that are expected to support management, has high external opportunities in terms of broader and permanent cooperation between parties, the possibility of developing tourist attractions with existing natural potential that has not been managed and becoming an educational medium to increase public awareness to maintain the sustainability of animals and the environment, and has low external threats in the form of the influence of the presence of toll roads, disturbances from the surrounding community and unfriendly attitudes, all of which can be overcome easily by socialitation. Referring to the existing condition of the Sumatera elephant education center tourist attraction, the coordinates are at point (0,82 ; 0,83) in quadrant I, the S-O (Strength-Opportunity) strategy will be implemented based on the strengths of the management to improve weaknesses by utilizing opportunities as optimally as possible to anticipate existing threats where the current management condition of the Sumatera elephant education center tourist attraction has strengths and development opportunities with the hope of maximizing the strengths and utilizing existing opportunities. So, the strategy that must be implemented in future development is to support an aggressive growth policy (growth-oriented strategy).